Write modern web apps with the MEAN stack : Mongo, Express, AngularJS, and Node.js - Dickey, Jeff, ....- ([Berkeley, CA] : Peachpit Press, 2015)
Traditionally, web applications have been architected so that the back-end houses all the front-end code. This has resulted in heavy projects that are difficult to manage and scale. This book will explain a new way to write web applications by treating the front-end as if it were a third-party (such as a mobile client). This book, written by a practicing MEAN developer, will take a holistic approach to using the MEAN JavaScript platform for creating modern web applications and lay out how to use the MEAN (Mongo, Express, AngularJS, and Node.js) set of tools to create a web application, from installation and setup of the tools to debugging and deploying your app. After an introduction to how web development is changing and the advantages of using the MEAN stack, the author jumps into an introduction to each tool and then dives into using the complete JavaScript-based application stack to build, test, and deploy apps.